Réseau francophone des living labs - 11ème édition du Festival des Arts Numériques - Trousse, Brigitte (2016)
Présentation de la 11ème édition du Festival des Arts Numériques du Réseau Francophonie Living Labs à Tunis (Tunisie). Coopération France-Québec
Keywords: France; Laboratoire vivant; Québec

Webinar | Place-based Social Innovation Through Living Labs - Institute Tamarack (2021)
This webinar includes the experiences and insights from two Québec-based organizations with an approach that yields a huge potential for transformative change.
Keywords: Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Québec; Webinaire

Le living lab, un intermédiaire d’innovation ouverte pour les territoires ruraux ou péri-urbains ? - Fasshauer, Ingrid; Zadra-Veil, Cathy (Innovations, 2020)
L’objectif de cet article est d’analyser une nouvelle forme organisationnelle, le living lab (LL) et sa capacité à favoriser l’innovation territoriale en milieu rural ou péri-urbain. A travers une revue de littérature et la mobilisation de la sociologie de l’acteur-réseau (Callon, 1986 ; Latour, 1987), nous positionnons les living labs comme intermédiaires d’innovation ouverte dont les caractéristiques permettent d’intégrer de nombreux acteurs hétérogènes, établissements publics, entreprises privées, associations et citoyens, sur des projets d’innovation. L’étude d’un LL rural met en évidence la capacité d’une telle structure à reconfigurer des réseaux d’acteurs pour proposer une série de tiers-lieux adaptés aux spécificités des territoires sur lesquels ils s’implantent. Cette recherche permet d’enrichir la réflexion la pérennisation des tiers-lieux ruraux et leurs spécificités par rapport aux espaces urbains.
Keywords: Collaboration; Innovation; Innovation ouverte; Laboratoire vivant; Living Labs; Réservé UdeM; Économie collaborative

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Keywords: Collaboration; Durabilité; Europe; Hackathon; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Médialab; Technologies; numérique

Framing improvements of public innovation in a living lab context: Processual learning, restrained space and democratic engagement - Fuglsang, Lars; Hansen, Anne Vorre (Research Policy, 2022)
Public innovation has received increasing attention in recent years. Experiments with new governance structures, such as New Public Management and New Public Governance, have challenged the traditional top-down, internally driven forms of innovation in the public sector and have entailed a search for new forms of open, collaborative and interactive innovation, implying a reframing of public innovation activities. However, introducing these new frames of innovation causes uncertainties in the public sector, necessitating better understanding of how public innovation can be changed to address societal needs. This paper uses materials from case studies of 21 public living labs across Europe to analyse the lessons that can be learned from public sector participation in living labs in terms of their contribution to reframing public innovation. The “frame” construct is used to analyse and provide an understanding of how participation in living labs helps public actors to reframe innovation and address public and societal needs. Three living lab framings for changing public innovation are identified (processual learning, restrained space and democratic engagement), and the degree of intensity of these framings with respect to involving stakeholders and addressing societal challenges is discussed. The paper contributes to knowledge of public sector innovation by extending previous accounts of how public innovation can be improved.
Keywords: Europe; Innovation publique; Laboratoire vivant; Libre accès; Living Labs